DETERMINANTS OF INFORMATION SYSTEM SUCCESS IN INDONESIA: SYSTEM REQUIREMENTS, TEAM CAPABILITIES, AND STAKEHOLDER INVOLVEMENT - Faidatul Hikmah; Sinung Suakanto (PT. Jurnal Center Indonesia Publisher, 2026)
Success in information system projects has a significant impact on the development of information technology. The research specifically explores the factors that can influence the success and failure of information system projects in Indonesia. The research method applied is a double linear regression analysis of a case study involving 67 information system projects that have been completed by various organizations and companies in Indonesia. Some of the major findings of this study cover critical aspects that have a significant impact on the performance of information system projects. Analysis of project information system requirements is identified as one of the key factors affecting the success of the project. Team capabilities, both in terms of technical skills and interpersonal coordination, are also important elements that correlate with project outcomes. The involvement of stakeholders throughout the project cycle has also proved to have a positive impact. It is understood that involving stakeholders actively can enhance a better understanding of user needs and minimize the risk of change of requirements in the middle of the way. By gaining in-depth insight into these key factors, this research makes valuable contributions to the planning, development, and implementation of future information system projects in Indonesia.